Analisis Penanganan Kesalahan Profesi Medis dan Kesehatan Dalam UU Nomor 17 Tahun 2023 Tentang Kesehatan Menurut Perspektif Hukum Kesehatan - Soge, Albertus D (Jurnal Hukum Caraka Justitia, 2023)
Health Law is a Lex Specialist law used to protect providers and receivers of health services. The new Health Law, namely the "Omnibus Law" Law Number 17 of 2023 concerning Health, makes changes in the regulation of handling medical and health professional errors. From the results of the discussion, it is concluded that the provisions for handling medical and health professional errors in Law Number 17 of 2023 have better protected medical and health personnel, but some provisions are not following the Health Law paradigm so that they can cause disadvantages on the side of providers and receivers of health services.